Upper segment/lower segment ratio and armspan-height difference in healthy Turkish children - (:unkn) unknown (My University, 2005)
AIM: The determination of body proportions is an important part of the clinical evaluation of children with short stature. The upper segment/lower segment ratio (US/LS ratio) and armspan-height difference is commonly used for this purpose. However, reference data are scarce in this respect, and available standards do not include standard deviations for the measurements. We aimed to establish the normal values for upper segment/lower segment ratio and armspan-height difference in Turkish children. METHODS: In the present study, height, upper and lower segment, and armspan were measured in 1302 healthy children (3-18 y). The age-related mean and standard deviation curves of the US/LS ratio and armspan-height difference were constructed for each sex. RESULTS: The mean values of the US/LS ratio in boys were decreased from 1.108 at 3 y to 0.984 at 10 y. The nadir of the US/LS ratio (0.922) was reached at age 15 y. In girls, the mean value of the US/LS ratio gradually decreased to less than 1 at 9 y of age (1 y earlier than in boys). The nadir of the US/LS ratio (0.946) was reached at age 13 y in girls (2 y earlier than in boys). Armspan was shorter than height as expected in younger ages, but became slightly longer at around age 12 in girls and boys. Unlike boys, the armspan-height difference did not change much after puberty in girls. CONCLUSION: US/LS ratio and armspan-height difference are practical parameters and easy to perform in any setting. We hope that these standards will aid clinicians in the evaluation of children with short stature.
Keywords: Female; Humans; Turkey; Adolescent; Male; Child; Child, Preschool; Reference Values; Arm; Body Height; Whites